Esterification of non-edible oil mixture in reactive distillation column over solid acid catalyst: experimental and simulation study - Ratna Dewi, Kusumaningtyas; Haniif, Prasetiawan; Brylian Rizky, Pratama; Dani, Prasetya; Anwaruddin, Hisyam (Penerbit Universiti Sains Malaysia, 2018)
Biodiesel is one of the promising energy alternatives to fossil fuel. Among the economical feedstocks of biodiesel is high free fatty acid (FFA) vegetable oil. Production of biodiesel from high FFA oils needs esterification reaction as the pre-treatment step. In this work, esterification reaction of high FFA non-edible oil mixture (used cooking oil, jatropha oil, and nyamplung seed oil) was conducted in reactive distillation (RD) column in the presence of solid acid tin(II) chloride catalyst. RD has potential to be applied at industrial scale. For this purpose, an accurate model is required to scale up the process, predict the RD performance and optimise the process. Experimental work, simulation study and validation were carried out in this work to determine the accurate model and simulation. In experimental work, esterification reaction was conducted by varying the reaction temperature and catalyst concentration. The simulation was performed using ASPEN PLUS V8.8 and validated with the experimental data. Based on the experiment, the optimum FFA conversion was 78.33%, obtained at temperature of 60ºC and catalyst concentration of 5% (w/w). The FFA conversion achieved from the simulation was 75.8%. The proximity between the simulation and experimental data demonstrated that this simulation has accurately predicted the conversion of FFA with less than 5% error.